Development and Implementation of In-House Pharmacogenomic Testing Program at a Major Academic Health System - Mroz, Pawel; Michel, Stephen; Allen, Josiah D.; Meyer, Tim; McGonagle, Erin J.; Carpentier, Rachel; Vecchia, Alexandra; Schlichte, Allyson; Bishop, Jeffrey R.; Dunnenberger, Henry M.; Yohe, Sophia; Thyagarajan, Bharat; et al. (Frontiers in Genetics, 2021)
Pharmacogenomics (PGx) studies how a person’s genes affect the response to medications and is quickly becoming a significant part of precision medicine. The clinical application of PGx principles has consistently been cited as a major opportunity for improving therapeutic outcomes. Several recent studies have demonstrated that most individuals (>90%) harbor PGx variants that would be clinically actionable if prescribed a medication relevant to that gene. In multiple well-conducted studies, the results of PGx testing have been shown to guide therapy choice and dosing modifications which improve treatment efficacy and reduce the incidence of adverse drug reactions (ADRs). Although the value of PGx testing is evident, its successful implementation in a clinical setting presents a number of challenges to molecular diagnostic laboratories, healthcare systems, providers and patients. Different molecular methods can be applied to identify PGx variants and the design of the assay is therefore extremely important. Once the genotyping results are available the biggest technical challenge lies in turning this complex genetic information into phenotypes and actionable recommendations that a busy clinician can effectively utilize to provide better medical care, in a cost-effective, efficient and reliable manner. In this paper we describe a successful and highly collaborative implementation of the PGx testing program at the University of Minnesota, a major academic medical center molecular genetic laboratory and selected pharmacies and clinics. We outline the development and technical validation of the in-house SNP based multiplex PCR based assay targeting 20 genes and 48 SNPs as well as a separate CYP2D6 copy number assay along with the process of PGx report design, results of the providers and pharmacists usability studies, the development of the software tool for genotype-phenotype translation and gene-phenotype-drug CPIC-based recommendations. Finally, we outline the process of developing the clinical workflow that connects the providers with the PGx experts within the molecular diagnostic laboratory and the pharmacy.